The Effectiveness of Lemongrass Aromatherapy in Reducing Dysmenorrhea Pain - Nahya, Fify Aulia; Rahmawati, Rahmawati (Genius Journal, 2025)
Introduction: Dysmenorrhea is a common menstrual complaint among adolescent girls, often impacting daily activities and emotional well-being. Non-pharmacological interventions, such as aromatherapy, are gaining attention for their potential in pain management. Lemongrass (Cymbopogon citratus) contains compounds with analgesic and calming properties that may reduce menstrual pain. Objective: This study aimed to evaluate the effectiveness of lemongrass aromatherapy in reducing dysmenorrhea pain intensity among adolescents. Method: An experimental study using a one-group pre-test post-test design was conducted at Al-Riyadl Islamic Boarding School, Cipanas, from March to May 2025. A total of 30 female adolescents were selected through accidental sampling. Pain intensity before and after the aromatherapy intervention was measured using the Numerical Rating Scale (NRS). Data were analyzed using univariate and bivariate methods. Result: The average pain intensity before aromatherapy was 15.50 (SD = 8.803), which significantly decreased to 1.23 (SD = 7.281) after treatment. Statistical analysis revealed a p-value < .001, indicating a significant reduction in pain. Conclusion: Lemongrass aromatherapy is effective in significantly reducing dysmenorrhea pain among adolescents. Its natural, accessible, and low-risk characteristics make it a promising complementary therapy, particularly in settings with limited access to conventional medical care.